Real-Time PCR Diagnostics Failure Caused by Nucleotide Variability within Exon 4 of the Human Cytomegalovirus Major Immediate-Early Gene - Lengerova, Martina (American Society for Microbiology, 2007)
Here we report how variability in the human cytomegalovirus genome sequence may seriously affect the outcome of its molecular diagnosis. A real-time quantitative PCR assay targeting the major immediate-early gene failed to detect the viral load in some, but not all, clinical samples from hematooncological patients. By amplification and sequencing the DNA across the regions targeted by this assay we found a number of nucleotide substitutions which accounted for decreased primer/probe binding. This decreased the sensitivity of the assay up to 1,000-fold.